High Resource Use among Adult Congenital Heart Surgery Admissions in Adult Hospitals: Risk Factors and Association with Death and Comorbidities. (13th February 2014) - Bhatt, Ami B.; Rajabali, Alefiyah; He, Wei; Benavidez, Oscar J.
Abstract Objective Adult hospitals are a common location of adult congenital heart disease (ACHD) admissions, including cardiac surgical admissions. Understanding the patterns and predictors of resource use could aid these institutions by identifying and targeting potentially modifiable determinants of high resource use (HRU). Our objectives were to examine resource use during adult congenital heart surgical admissions in adult hospitals, determine the association of HRU with mortality, and identify risk factors for HRU. Design Population‐based retrospective study We obtained data from the Nationwide Inpatient Sample 2005–2009 and examined ACHD surgical admissions ages 18–49 years (n = 16 231). Outcome Measures We defined HRU as admissions with >90th percentile for total hospital charges. Results Despite representing 10% of admissions, HRU admissions accounted for 32% of total charges. HRU admissions had a higher mortality rate (9.7% vs. 1.8%, P < .001). Multivariable analysis demonstrated that HRU is associated with government insurance adjusted odds ratio (AOR) 2.0 (95% confidence interval [CI] 1.6, 2.4), emergency admissions AOR 3.9 (95% CI 3.1, 4.8), complications AOR 4.2 (95% CI 3.3, 5.2), renal failure AOR 1.8 (95% CI 1.4, 2.2), congestive heart failure AOR 1.2 (95% CI 1, 1.4), surgical complexity risk category‐2 AOR 2.0 (95% CI 1.0, 3.6), and category‐3+ AOR 2.3 (95% CI 1.4, 3.8). Conclusions HRU admissions for adult congenital heart surgery consumed a disproportionate amount of resources and were associated with higher mortality. HRU risk factors included nonelective admissions, government insurance, heart failure, surgical complexity, renal failure, and complications. Complications, if preventable, may be a target for improvement strategies to decrease resource use. Other risk factors may require a broader patient care approach.